Global problems in education as a research object in international databases: a historical perspective - S. N. Sinegubov; I. K. Tsalikova; S. V. Pakhotina; N. I. Sabaeva; I. M. Kungurova (Образование и наука)
Introduction. Global problems of modernity and globalisation are appealing to scientists as a research subject not only for understanding their nature, development, and manifestations in various spheres of life (in the case of our study, in education) but also because a comprehensive analysis is essential to combat them. Aim. The study aimed to trace the history of scientific research on the impact of global issues on the education system. It utilised bibliometry to conduct a qualitative content analysis of selected works to identify existing research trends within the topic and factors influencing the research agenda both in Russian Federation and abroad. Methodology and research methods. The research utilizes bibliometric methods and qualitative content analysis of publications (articles, conference proceedings, monographs, and reports) from open-access scientific journals at the final stage of publication. The study also examines statistical reports from the international Scopus database for the period from 1978 to 2023, selected based on bibliometric criteria. Papers were analysed and classified according to their publication periods and the number of citations they received. Based on the results of a qualitative content analysis comparing scientific agendas worldwide and in Russian Federation, the study identified the topics, conceptual foundations, and key participants influencing the resolution of global education issues across various historical periods. Results. Four waves of interest in this topic were identified: 1988–1999, 2000–2012, 2013–2018, and 2019–2023. From 1988 to 1999, all studies can be broadly categorised into two groups: teaching methods and organisation of educational activities. The development of specific trends in the study of global education problems began only between 2000 and 2012. From 2013 to 2018, scientists focused on restructuring the educational process in new conditions. From 2019 to 2023, the focus shifted to the impact of the COVID-19 pandemic on the organisation and transformation of the educational process. It has been established that the thematic focus of research by Russian scientists and the international scientific community as a whole differs. The authors cite and analyse the possible historical reasons for this divergence. Scientific novelty is ensured by the absence of similar research in the international information space. Practical significance lies in the necessity, given the current socio-economic situation, to highlight global education issues for the purpose of planning and coordinating research efforts.